Dinuclear Ag(I) Complex with Cyanuric Acid Ligand: Synthesis, Crystal Structure and Luminescent Properties - Zhu, Baoyong (Asian Journal of Chemistry, 2010)
The dinuclear Ag(I) complex Ag2(CA)4·H2O (CA = cyanuric acid), has been synthesized hydrothermally. The crystal structure is of monoclinic, space group C2/c with a = 9.627(5), b = 12.500 (5), c = 19.161(5) Å, (C3H2N3O3Ag2)4·H2O. Mr = 764.08, V = 2232.1(1) Å3, Dc = 2.274 g/cm3, F(000) =1496, μ = 1.856 cm-1 and Z = 4, the final R = 0.0252, WR = 0.0611 and S =1.015 for 2165 observed reflections with I > 2s(I), The cyanuric acid ligand came from the in situ hydrolysis of melamine and cyanuric chloride under the hydrothermal conditions. The X-ray crystal structure analysis indicates that the complex is a 3D coordinated framework, which is constructed by the combination of coordination bonds, hydrogen bonds, p-p stacking interaction and Ag···Ag interactions. Fluorescent analyses of the dinuclear Ag(I) complex show intense photo-luminescence at 440 nm in the solid state, which means the complex may be potential candidate for photoactive material.